Emergency department utilisation by homeless children in Dublin, Ireland: a retrospective review. Issue 1 (16th March 2022) - O' Brien, Niamh; Quinn, Nuala; Joyce, Birgitta; Bedford, Helen; Crushell, Ellen
Abstract : Introduction: Despite increasing prevalence, European family homelessness remains under-researched. Methods: A retrospective review was performed of homeless children attending a paediatric emergency department in Dublin, Ireland, from 1 January 2017 to 31 December 2020. Comparison was made with a random cohort of 1500 non-homeless paediatric attendances in 2019. Homelessness was defined using the European Typology of Homelessness and Housing Exclusion, including those with addresses of no fixed abode, government homeless accommodation and certain residential settings. The objectives were to compare presentations between homeless and non-homeless children. We were interested in determining differences regarding demographics, healthcare utilisation, clinical presentation and outcomes. Results: Of 197 437 attendances 3138 (1.59%) were homeless. Compared with the non homeless, homeless children were less likely to be ethnically Irish (37.4% vs 74.6%, p<0.001) or have been born in Ireland (82.3% vs 96.2%, p<0.001). Irish Travellers (3% vs 0.8%), Roma (22.5% vs 2.4%) and black (21.1% vs 4.2%) ethnicities were over-represented (p<0.001) in the homeless cohort. Homeless children were younger (age <12 months: 26% vs 16%; p<0.001), less likely to be fully vaccinated (73.6% vs 81.9%, p<0.001) and have registered general practitioners (89.7% vs 95.8%, p<0.001). They were more likely to represent within 2 weeks (15.9% vs 10.5%, p<0.001), and use ambulance transportation (13.2% vs 6.7%, p<0.001). Homeless children had lower acuity presentations (triage category 4–5: 47.2% vs 40.7%, p<0.001) and fewer admissions (5.9% vs 8.4%, p<0.001) than non-homeless children. Discussion: Infants, Irish Travellers, Roma and black ethnicities were over-represented in homeless presentations. Homeless children had increased reliance on emergency services for primary healthcare needs.